Local E-Government Sophistication in Ecuador: The Case of the Manabí Province - Dias, Gonçalo Paiva (2020)
The present study aims to review the status of local e-government sophistication in the province of Manabí (Ecuador). Website content analysis and a three-dimensional maturity model (e-information, e-services, e-participation) are used to assess the state of maturity of the 22 cantons that compose the province. Descriptive statistics, correlation analysis and clustering technics are used to analyze results. The comparison of the results with previous studies in other countries allows the conclusion that there is still à significant margin for improvement in the studied cantons, namely in the dimensions related to electronic service delivery and citizen's participation. The results also show the existence of a hierarchy between the three dimensions of analysis and that different profiles of municipalities exist in what concerns the balance between those three dimensions. These last two findings are consistent with other studies that used the same methodology in other countries.